Spycat and the paper chase. - Soh, Yu Xian. (2011)
This report is basically a summary of the animation project Spycat and the Paper Chase. The report starts with brief introduction of the animation to establish a general idea for viewers. It then explains the source of inspiration in terms of visual style by comparing to some of the industry and student projects. Next, it elaborates each stage in the entire working pipeline, including pre-production, production, and post-production. After that, it also discusses the difficulties and problems faced by the production team and individual. In the end, the report wraps up by concluding experience and expectation.